Зміни в управлінні охороною праці шляхом застосування євростандартів - Кортяк, Є. Ю. (ХНУРЕ, 2019)
The given work is about the changes in the management of labor protec-tion, after the signing of an agreement on association between Ukraine and the EU. Main problems of pricing strategies formation were investigated. Moreover, the problems of creating the OSH management system were considered and some useful tips on modernization of occupational health were given in this work.